Contribution of reading comprehension ability and learning motivation to writing - Ria Wati; Atmazaki Atmazaki; Tressyalina Tressyalina (International Conferences on Educational, Social Sciences and Technology)
The purpose of this description. First, the contribution of reading comprehension of writing exposition texs ability. Second, the contribution learning motivation to writing exposition texs ability. Thirth, the contribution of reading comprehension ability and learning motivation to writing exposition texs ability students of class X SMA Negeri 2 Pariaman. This research was a quantitative research using correlational method. The results of the research are. The reading comprehension ability contribute significant by 87% to writing exposition texs ability. The learnig motivation contribute significant by 25,9% to writing exposition texs ability. The reading comprehension ability and learnig motivation together contribute by 87,1% to the writing exposition texs ability. Can conclusion is reading comprehension ability and learnig motivation together contribute and significant relationship to writing exposition ability.